H. Ramsden, The 1898 movement in Spain. Towards a reinterpretation with special reference to "En torno al casticismo" and "Idearium español". Manchester University Press, Manchester, 1974; 212 pp. - Gómez Martínez, José Luis (El Colegio de México, 1977)
Se reseñó el libro: The 1898 movement in Spain. Towards a reinterpretation with special reference to "En torno al casticismo" and "Idearium español".